Artistic Originality of the Historical Story "Taras Bulba" in the Collection "Mirgorod" - E.V.Сhjen; U.Fayzullayeva (Zien Journals, 2022)
The article examines one of the important and complex issues in the work of N.V. Gogol - his understanding of history and historical personality, as well as their artistic embodiment in the collection "Mirgorod".
Keywords: Historical views of the writer, Gogol's narrative, historical songs, the collection